Effect of Pre-Treatment by Organic Solvent on Leaching of Copper from Waste Printed Circuit Boards (WPCBs) - Basha S.M.; Hariprasad S.; Bharani B.; Verma H.R.; Singh K.K. (My University, 2025)
Selective dissolution of copper from waste printed circuit boards (WPCBs) using atmospheric, microwave, and pressure leaching techniques has been investigated. A critical comparison of these three different methods was analyzed based on their leaching efficiency of the copper. The hydrothermal autoclave reactor was used for pressure leaching of printed circuit boards (PCBs) powder and also organic solvent treated PCBs were utilized instead of Parr high pressure reactor. Dimethylacetamide (DMAc) and Dimethylformamide (DMF) were used for organic swelling of 1 cm × 1 cm PCBs. DMAc at optimum conditions (temperature: 140 ºC, S/L ratio: 300 g/L, time: 6 h) displayed better dissolution of epoxy resins than that of DMF and facilitates the easy separation of metallic parts from non-metallic parts of PCBs. The percentage of copper in PCBs powder, DMF and DMAc treated PCBs was found to be 21, 46.02 and 78.75 % respectively. Pressure leaching of copper was carried out using two different oxidizing agents such as nitric acid and hydrogen peroxide. It has been identified that HNO3 found to be better oxidizing agent at 140 ºC in an autoclave as compared to H2O2. The Optimized conditions for pressure leaching of PCBs powder were temperature of 140 ºC with S/L ratio of 50 g/L using 15% HNO3 oxidizing agent and 3M H2SO4 concentration in time of 90 min. The leaching of copper from metal clads obtained after organic swelling with DMAc showed that the leaching efficiency is 96.96% with 5% HNO3 along with 3M H2SO4, S/L ratio of 50 g/L and time of 90 min at 140 ºC. The amount of oxidizing agent required for pressure leaching of DMAc treated PCBs is less when compared to pressure leaching of PCB powder. © 2023 SPIE.